The origins of multicellular organisms. Issue 1 (20th January 2013) - Niklas, Karl J.; Newman, Stuart A.
SUMMARY Multicellularity has evolved in several eukaryotic lineages leading to plants, fungi, and animals. Theoretically, in each case, this involved (1) cell‐to‐cell adhesion with an alignment‐of‐fitness among cells, (2) cell‐to‐cell communication, cooperation, and specialization with an export‐of‐fitness to a multicellular organism, and (3) in some cases, a transition from "simple" to "complex" multicellularity. When mapped onto a matrix of morphologies based on developmental and physical rules for plants, these three phases help to identify a "unicellular ⇒ colonial ⇒ filamentous (unbranched ⇒ branched) ⇒ pseudoparenchymatous ⇒ parenchymatous" morphological transformation series that is consistent with trends observed within each of the three major plant clades. In contrast, a more direct "unicellular ⇒ colonial or siphonous ⇒ parenchymatous" series is observed in fungal and animal lineages. In these contexts, we discuss the roles played by the cooptation, expansion, and subsequent diversification of ancestral genomic toolkits and patterning modules during the evolution of multicellularity. We conclude that the extent to which multicellularity is achieved using the same toolkits and modules (and thus the extent to which multicellularity is homologous among different organisms) differs among clades and even among some closely related lineages.